Peran Harga Diri dalam Mengembangkan Kecemasan Sosial - Siti Khusnul Faizah (Taqorrub: Jurnal Bimbingan Konseling dan Dakwah, 2022)
Today, anxiety is a growing phenomenon as people face increasingly stressful situations. Therefore, among the various forms of manifestation, there is social anxiety. This type of anxiety generally begins in adolescence, when the personality is still being formed and when the teenager is increasingly interested in getting confirmation from others. When he is being analyzed by others, a teenager is afraid of failure and is embarrassed when things don't go as they should, he is afraid of being judged by others for possible minor mistakes and, thus, anxiety arises. In other words, people with low self-confidence and lack of confidence in their abilities have low self-esteem and can easily develop this form of anxiety. As we have already mentioned, social anxiety is caused by the fear of being criticized by others, by the fear of being evaluated incorrectly, by feelings of shame, being in the presence of strangers, etc. All these social contexts are the backdrop for unexplained individual restlessness which can lead to physical symptoms like excessive sweating, shaking, palpitations, blushing etc. Self-esteem is very important here because it is very important how the subject sees himself in social situations. Thus, if a person feels unable to deal with situations that are considered difficult and lacks confidence in his own abilities, which means he has low self-esteem, this behavior is very likely to lead to social debut. worry. Therapy sessions help reduce and even eliminate this disorder. There are certain techniques that consist of dealing with the problem until the subject begins to feel comfortable with aspects of normal life that were formerly considered episodes of anxiety.